2009
DOI: 10.1176/appi.psychotherapy.2009.63.4.319
|View full text |Cite
|
Sign up to set email alerts
|

The Supporting Alliance in Child and Adolescent Treatment: Enhancing Collaboration Among Therapists, Parents, and Teachers

Abstract: Research indicates that the therapeutic alliance between therapist and pediatric patient is most effective in the context of a productive supporting alliance--an alliance encompassing the network of relationships among therapists, parents and teachers. In this essay, we develop a model of the supporting alliance, arguing that the child's primary relationships with various parties (therapists, teachers, and parents) imply a set of secondary relationships among those parties (parent-therapist, therapist-teacher,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Despite such competing agendas and levels of integration within the school curriculum and ethos, successful health education in schools is conducive to the schools capacity, planning, and support of the initiative, the degree to which the initiative is viewed as useful and relevant within the school ethos, and levels of teacher and management promotion of the initiative within the school (Peterson et al 2000, MacDonald and Green 2001, Buston et al 2002, Dusenbury et al 2003, Fagan and Mihalic 2003, Healy 2004. Teachers are valuable partners in the integration of health and social material within classrooms, and thereby offer the potential for sustaining longer term effects in targeting health behaviors (Smolak et al 2001, Adi et al 2007, Stormont et al 2008, Feinstein et al 2009, Ringwalt et al 2010, Wolmer et al 2011, Franklin et al 2012. It remains evident that teachers also play a significant role in the interpretation of health-related material and the subsequent translation of curriculum into classroom activities Prosser 1996, Trigwell et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Despite such competing agendas and levels of integration within the school curriculum and ethos, successful health education in schools is conducive to the schools capacity, planning, and support of the initiative, the degree to which the initiative is viewed as useful and relevant within the school ethos, and levels of teacher and management promotion of the initiative within the school (Peterson et al 2000, MacDonald and Green 2001, Buston et al 2002, Dusenbury et al 2003, Fagan and Mihalic 2003, Healy 2004. Teachers are valuable partners in the integration of health and social material within classrooms, and thereby offer the potential for sustaining longer term effects in targeting health behaviors (Smolak et al 2001, Adi et al 2007, Stormont et al 2008, Feinstein et al 2009, Ringwalt et al 2010, Wolmer et al 2011, Franklin et al 2012. It remains evident that teachers also play a significant role in the interpretation of health-related material and the subsequent translation of curriculum into classroom activities Prosser 1996, Trigwell et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, research by Sheridan et al (2010) into parental perceptions of treatment identified that therapist who exhibit non-judgmental, nonblaming qualities improve the comfort that parents experience with the therapeutic process. Feinstein et al (2009) identify a paucity of professional literature providing guidance to clinicians on how best to develop and sustain effective parent-clinician alliances. However, based on the literature that has been discussed and the investigators' personal reflections and experiences in practice, developing a richer understanding of how guilt and blame may be influencing the parent-clinician relationship is likely to be an important instrumental step for clinicians seeking to extend their empathy and engagement with family members and clients.…”
Section: Guilt and Blamementioning
confidence: 99%
“…With Children of Conflicted Caregivers (Garber, 2004); -Therapist Alliance-Building Behavior Within a Cognitive Behavioral Treatment for Anxiety in Youth (Creed & Kendall, 2005); -Prediction of Cognitive Behavior Treatment Outcome for Children with Anxiety Disorders: Therapeutic Relationship and Homework Compliance (Hughes & Kendall, 2007); -Youth working alliance: A core clinical construct in need of empirical maturity (Zack, Castonguay, & Boswell, 2007); -The Supporting Alliance in Child and Adolescent Treatment: Enhancing Collaboration Among Therapists, Parents, and Teachers (Feinstein, Fielding, Udvari-Solner, & Joshi, 2009); -The parent-child-therapist alliance: A case study using a strategic approach (Naidu & Behari, 2010); -Therapist perspectives on the therapeutic alliance with children and adolescents (Campbell Clinical Trial (Ormhaug, Wentzel-Larsen, Jensen, & Shirk, 2014).…”
Section: Características Da Aliança Terapêutica Na Psicoterapia De Crmentioning
confidence: 99%
“…Essa categoria abrangeu estudos que se destinaram a descrever características da aliança terapêutica estabelecidas no processo psicoterápico com crianças (Campbell & Simmonds, 2011;Chu et al, 2004;Creed & Kendall, 2005;Crenshaw & Kenney-Noziska, 2014;Digiuseppe, Linscott, & Jilton, 1996;Feinstein, Fielding, Udvari-Solner, & Joshi, 2009;Fox, 2012;Garber, 2004;Hughes & Kendall, 2007;Hudson et al, 2014;Jensen et al, 2012;Kazdin & Durbin, 2012;Langer, McLeod, & Weisz, 2011;McLeod, 2011;Naidu & Behari, 2010;Zack, Castonguay, & Boswell, 2007). Três estudos apontaram que a aliança, na psicoterapia de crianças, é moderada por características do paciente, do terapeuta e da família (Kazdin & Durbin, 2012;McLeod, 2011;Zack, Castonguay, & Boswell, 2007).…”
Section: Instrumentos Para Avaliar Aliança Terapêutica Com Criançasunclassified